Sistem Informasi Penggalangan Dana Pada Panti Asuhan Al-Arif Padang Matinggi Rantauprapat Berbasis Web - Kiki Mayanggi (Universitas Labuhanbatu, 2021)
One of the noble actions is charity, because by doing it we can help ease the burden of people who are more in need. Social home is one of the places established to accommodate and care for abandoned children. To meet all the daily needs of the orphanage needs a helping hand from various parties. This study took a case study of orphanages in rantauprapat city. When conducting research into the field, there are still many social institutions that do not have a website as a means of fundraising. Currently panti only receive donations from the surrounding community. One way out to meet the needs of foster children is to build a fundraising system. The results obtained from this application in the form of a web-based fundraising information system. When the design process using waterfall method with structured modeling.